Digitalization Strategy and Convergence of Media Adaptation in the Digital Era (case study on TVRI Yogyakarta). Issue 1 (January 2021) - Jean, N; Ispandriarno, L S
Abstract: Recently, the digital era is evidenced by new technologies that contribute to the development of all activities of human life. Currently, the television industry is affected by the presence of digital television and media convergence due to the rapid technological development and the existence of the 4.0 industry revolution. The media industry is required to move on with the updated technology to provide its content in a good and rapid way. This study aims to analyze the issues facing TVRI Yogyakarta while trying to adapt the digitalization strategy and convergence of media in the digital era. In this study, the researcher used a qualitative method. The results found out that digital technology uses a spectrum of higher quality in terms of video, audio, and television data sets, Digital Television Broadcasting (DVB) can support more than one program on the same bandwidth channel. Shifting from analog to digital and competition are some of the problems faced by TVRI Yogyakarta while trying to adapt the digitalization strategy. To avoid facing digitalization strategy challenges, all Public Broadcasting Institutions engaged in television need to prepare themselves well to remain competitive and show their quality.